Activated kinase screening identifies the IKBKE oncogene as a positive regulator of autophagy. Issue 2 (1st February 2019) - Leonardi, Margherita; Perna, Eluisa; Tronnolone, Serena; Colecchia, David; Chiariello, Mario
ABSTRACT: Macroautophagy/autophagy is one of the major responses to stress in eukaryotic cells and is implicated in several pathological conditions such as infections, neurodegenerative diseases and cancer. Interestingly, cancer cells take full advantage of autophagy both to support tumor growth in adverse microenvironments and to oppose damages induced by anti-neoplastic therapies. Importantly, different human oncogenes are able to modulate this survival mechanism to support the transformation process, ultimately leading to 'autophagy addiction'. Still, oncogenic signaling events, impinging on the control of autophagy, are poorly characterized, limiting our possibilities to take advantage of these mechanisms for therapeutic purposes. Here, we screened a library of activated kinases for their ability to stimulate autophagy. By this approach, we identified novel potential regulators of the autophagic process and, among them, the IKBKE oncogene. Specifically, we demonstrate that this oncoprotein is able to stimulate autophagy when overexpressed, an event frequently found in breast tumors, and that its activity is strictly required for breast cancer cells to support the autophagic process. Interestingly, different oncogenic pathways typically involved in breast cancer, namely ERBB2 and PI3K-AKT-MTOR, also rely on IKBKE to control this process. Ultimately, we show that IKBKE-dependent autophagy is necessary for breast cancer cell proliferation, suggesting an important supporting role for this oncogene and autophagy in these tumors. Abbreviations: AAK1: AP2 associated kinase 1; AMPK: 5ʹ-prime-AMP-activated protein kinase; AKT1: AKT serine/threonine kinase 1; BAF: bafilomycin A1 ; CA: constitutively activated; CDK17: cyclin dependent kinase 17; CDK18: cyclin dependent kinase 18; CHUK: conserved helix-loop-helix ubiquitous kinase; EGF: epidermal growth factor; ERBB2: erb-b2 receptor tyrosine kinase 2; FGF: fibroblast growth factor; FM: full medium; GALK2: galactokinase 2; IKBKB: inhibitor of nuclear factor kappa B kinase subunit beta; IKBKE: inhibitor of nuclear factor kappa B kinase subunit epsilon; IKK: IκB kinase complex; KD: kinase dead; MAP1LC3B/LC3B: microtubule associated protein 1 light chain 3 beta; MAPK1: mitogen-activated protein kinase 1; MAPK15: mitogen-activated protein kinase 15; MTORC1: mammalian target of rapamycin kinase complex 1; myr: myristoylation/myristoylated; NFKBIA: NFKB inhibitor alpha; PDGF: platelet derived growth factor; PFKL: phosphofructokinase, liver type; PRKAA1: protein kinase AMP-activated catalytic subunit alpha 1; PRKCD: protein kinase C delta; SQSTM1: sequestosome 1; TBK1: TANK binding kinase 1; TNBC: triple-negative breast cancer; TSC2: TSC complex subunit 2; WB: western blot; WT: wild-type.